Priklandnye osnovy technologii proektirovanija makrociklov tipa godicnogo v komandno-igrovych vidach sporta - Sacharova, M. V. (Teorija i Praktika fiziceskoj Kul'tury, 2004)
The technology of designing of a certain stage of training of athletes consists of the number of logically consecutive operations. The author has checked up the technique of designing with the help of Rugby footballteam.